Shaping Factor of the Normative Behavior of the Catholic Believers - Driyanto, Yohanes; Soelasih, Yasintha (Bina Nusantara University, 2023)
The research aimed to examine the effect of Jesus’ communication, attitude, and action on the perception and normative behavior of Catholics. The level of interpretation and observance of the Canon Law by Catholic believers was relatively low. The Bible told about Jesus conveying His teaching by putting it down into communication, His way of having an attitude, and His example in taking action. The research was based on the cognitive-affective-conative model. Cognitive referred to knowledge or information conveyed commonly in communication, affective was related to emotion or feeling manifested in attitude, and conative was about doing or action. Normative behavior was the way people behave, taking the basis of their understanding and feeling in accordance with the Canon Law. The novelty of research on the application of the concept of consumer behavior in the life of the Church was based on the teachings of Jesus. Data collection was carried out by non-probability with purposive sampling. The questionnaires were distributed using G-form via WhatsApp, and 297 respondents participated. The data were then processed using Structural Equation Modeling with the Smart PLS 3.0 application to test the reliability, validity, and hypotheses. The results of the hypothesis test show that all are rejected. The variables of communication, attitude, action, believer’s perception, and normative behavior on the object of religion show that the theory of behavior on these variables does not support previous research.